2009
DOI: 10.1016/j.jpowsour.2009.04.044
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phosphine in syngas on Ni–YSZ anode-supported solid oxide fuel cells

Abstract: a b s t r a c tNi-YSZ cermet is commonly used as the anode of a solid oxide fuel cell (SOFC) because it has excellent electrochemical performance, not only in hydrogen fuel, but also in a clean blended synthetic coal syngas mixture (30% H 2 , 26% H 2 O, 23% CO, and 21% CO 2 ). However, trace impurities, such as phosphine (PH 3 ), in coalderived syngas can cause degradation in cell performance [J.P. Trembly, R.S. Gemmen, D.J. Bayless, J. Power Sources 163 (2007) 986-996]. A commercial solid oxide fuel cell was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 17 publications
5
64
1
Order By: Relevance
“…As in previous studies, [3][4][5][6][7][8][9][10][11][12][13] this coating yields XRD spectra consistent with nickel phosphide phases.…”
Section: Resultssupporting
confidence: 72%
“…As in previous studies, [3][4][5][6][7][8][9][10][11][12][13] this coating yields XRD spectra consistent with nickel phosphide phases.…”
Section: Resultssupporting
confidence: 72%
“…Each can cause premature degradation of SOFC materials. 6,[9][10][11][12][13][14][15] Many, if not all, of these impurities have been studied extensively using electrochemical methods. Techniques such as electrochemical impedance spectroscopy (EIS) and voltammetry consistently show how exposure to these individual contaminants lead to performance degradation with differing levels of severity and reversibility.…”
mentioning
confidence: 99%
“…Besides, the nickel phosphide of Ni 5 P 2 was believed to be produced in a pure hydrogen atmosphere as described by Eq. (2) [23]. It seems the formation of nickel phosphide degrades the cell to a larger extent than that caused by nickel phosphate.…”
Section: Effects Of Ph 3 and Ch 3 CL On Cell Performance At Simulatedmentioning
confidence: 99%
“…It seemed that the presence of PH 3 at a low concentration can unexpectedly cause a larger degradation rate under similar conditions, which may result from effects of the cell dimension or configuration. Xu et al [23] indicated that a constant of 0.46 mV h ±1 degradation in cell voltage was induced by the addition of 10 ppm PH 3 to coal syngas at 800 C. Zhi et al [13] studied the cell performance in a simulated coal-derived gas containing 20 ppm PH 3 at 900 C and their results revealed that sharp degradation occurred after the addition of 20 ppm PH 3…”
Section: Introductionmentioning
confidence: 99%